On Subtle Bodies, Out-of-Body Experiences, and Apparitions of the Living: A Review of Ernesto Bozzano’s Study of "Bilocation": La Bilocazione: Sdoppiamenti, Viaggi Astrali, Esperenze Extracorporee by Ernesto Bozzano - Alvarado, Carlos S.; Biondi, Massimo (Journal of Scientific Exploration, 2022)
For many years there have been phenomena such as apparitions of the living, photographs of the living at a distance, near-death experiences, emanations of light from the dying, fog, or incorporeal “doubles,” which have suggested the existence of a spirit, or “subtle body,” able to separate itself from the physical body, sometimes bringing consciousness with it. This idea also underpins the projection model for Out-of-Body Experience (OBE) cases, which has an interesting history (Alvarado, 2009, 2011, 2019). Here I briefly review that concept through the analysis of a work written by the Italian student of psychic phenomena Ernesto Bozzano, published for the first time in 1934 (Bozzano, 2020) and recently re-edited in the original language by Golem Libri, a young publishing house specializing in “psychic” topics. In discussing this book my approach is mainly historical. I hope both to help modern readers to get more acquainted with Bozzano’s work, and to highlight those passages that deepen our understanding of specific aspects of the topic, especially with reference to the ideas on OBEs published before the 1930s. I am convinced that while the issues discussed by Bozzano have a limited value today, they can stimulate further discussions.